The characteristic of Phitoplankton’s community of the western part of Northern Caspiy - S. A. Guseinova; V. F. Zaitsev (Юг России: экология, развитие, 2015)
Phitoplankton - one of the most significant groups of organisms water, being the basic producer of organic substance in the seas and oceans. Development of other trophic levels depends on its structure and quantity indicators in water ecosystems and their biological efficiency.